Predator-prey interactions in aerobic granulation systems - Chan, Siew Herng (2018)
Predation by protozoa can impact bacterial communities by controlling their biomass and alter the community species composition. Bacterial communities are essential for the functioning of most ecosystems including engineered systems such as activated floccular sludge, where bacteria are responsible for biological nutrient removal and flocculation. Activated floccular sludge is often utilized to cultivate aerobic granules over long periods of time. Although the formation of granules has been optimized by controlling physical factors, the instability of aerobic granules remains a challenge for its implementation in full-scale wastewater treatment systems. While it has been hypothesised that protozoa are important in the formation of granules, no studies have characterized the abundance and diversity of protozoa during aerobic granulation. In this study, the impact of protozoa on microbial communities was monitored. Sessile ciliates were reported to be the most abundant protozoa that colonized the surfaces of granules. These ciliates consume suspended bacteria and are also hypothesized to act as a form of substratum for bacteria; colonization. Here, four bioreactors seeded with activated floccular sludge were operated for aerobic granulation for 11 weeks to better understand the roles of protozoa during the formation of aerobic granules. The abundance and diversity of protozoa decreased initially due to reduction in settling time. Upon the formation of granules, sessile ciliates became the dominant group of protozoa with gradual increase in abundance. However, microbial community analysis and correlation studies demonstrated that protozoa did not have a significant role in granule formation. In contrast, bacteria, particularly Candidatus Accumulibacter, were suggested to have a greater role in the formation of granules. The role of predation by protozoa on the formation of granules was further explored through the inhibition of protozoa in floccular sludge performed to investigate if aerobic granulation would be affected without protozoa. The absence of protozoa did not significantly affect the formation of granules from floccular sludge. Similar to the experiments following the changes in the community composition, it was also observed that Candidatus Accumulibacter was highly dominant when granules were formed in the treated sludge. In addition, inhibition of protozoa, including sessile ciliates on the surface of pre-formed granules, also did not result in disintegration of granules. Granules with and without sessile ciliates continued to maintain their granular appearance and size. Overall, the data suggested that protozoa did not play a dominant role in granulation and it was the change in sludge morphology that selected for the dominance of sessile ciliates in granules. Aerobic granules and activated floccular sludge comprised of high species diversity. Therefore, to better define the mechanisms that drive the interaction between microbial communities and predators, a mixed species biofilm system composed of Pseudomonas aeruginosa, Klebsiella pneumoniae and Pseudomonas protegens was subjected to protozoan grazing by the model ciliate, Tetrahymena pyriformis. It was found that grazing sensitive strains, K. pneumoniae and P. protogens, gained associational resistance from the grazing resistant P. aeruginosa. This resistance was partly due to the production of rhamnolipids, however results showed that there were other unidentified factors that provide P. aeruginosa resistance to predation.